2020
DOI: 10.1038/s41598-020-71290-6
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of freshening trend of Antarctic Bottom Water in the Australian-Antarctic Basin during 2010s

Abstract: The Antarctic continental margin supplies the densest bottom water to the global abyss. From the late twentieth century, an acceleration in the long-term freshening of Antarctic Bottom Waters (AABW) has been detected in the Australian-Antarctic Basin. Our latest hydrographic observations reveal that, in the late 2010s, the freshening trend has reversed broadly over the continental slope. Near-bottom salinities in 2018–2019 were higher than during 2011–2015. Along 170° E, the salinity increase between 2011 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 33 publications
4
28
0
Order By: Relevance
“…Nevertheless from 2010 to 2018, AABW regained its salinity (Figure 2B). This is consistent with the observations by Aoki et al (2020b) who reported reversal of freshening of AABW during 2018-19 in comparison with the previous decades. The observed freshening is pronounced at 80 • E, in contrast to the increase in salinity to the east of 115 • E (Aoki et al, 2020b).…”
Section: Observations On Freshening and Warming Of Antarctic Bottom Watersupporting
confidence: 93%
See 2 more Smart Citations
“…Nevertheless from 2010 to 2018, AABW regained its salinity (Figure 2B). This is consistent with the observations by Aoki et al (2020b) who reported reversal of freshening of AABW during 2018-19 in comparison with the previous decades. The observed freshening is pronounced at 80 • E, in contrast to the increase in salinity to the east of 115 • E (Aoki et al, 2020b).…”
Section: Observations On Freshening and Warming Of Antarctic Bottom Watersupporting
confidence: 93%
“…This is consistent with the observations by Aoki et al (2020b) who reported reversal of freshening of AABW during 2018-19 in comparison with the previous decades. The observed freshening is pronounced at 80 • E, in contrast to the increase in salinity to the east of 115 • E (Aoki et al, 2020b). Furthermore from 2018 to 2020, the AABW lost its salinity by ∼0.002 and became warmer by ∼0.04 • C suggesting re-freshening and warming from 2018 to 2020, though this freshening was not as intense as that in 2010.…”
Section: Observations On Freshening and Warming Of Antarctic Bottom Watersupporting
confidence: 93%
See 1 more Smart Citation
“…A relatively small temperature increase in the water transformation term (up to 0.1°C) is observed in a few sections (e.g., 150°E) below the 28.1 kg m −3 isopycnal, where the upper overturning circulation is unlikely to affect the temperature. This change may be related to a modified mixing ratio of the locally produced AABW (22,32) and salinification of the ambient Ross Sea Bottom Water (34). By the five-section average (Table 1), the warming of Upper CDW associated with the poleward shift of the SB (0.31°C) is about 70% (0.21°C) due to the frontal shift term and about 30% (0.10°C) due to the water transformation term.…”
Section: Isopycnal Changes Due To Frontal Shifts and Enhanced Overturning Circulationmentioning
confidence: 99%
“…AABW is the densest water mass found globally. Made of cold and saline water, it occupies a large portion of the World Ocean's sea floor (Johnson, that the deep Southern Ocean has been warming and freshening over the past decades, in particular in the East Antarctic basins (Aoki et al, 2005;Rintoul, 2007), while Aoki et al (2020) revealed a reversal of the trend after 2010. As modifications of AABW are expected to have far reaching consequences, such changes illustrate the need for trustworthy projections of future polar climate.…”
Section: Introductionmentioning
confidence: 99%